Diagnóstico laboratorial da neurocisticercose: padronização e avaliação do método ELISA utilizando a proteína de 14kDa da Taenia crassiceps como modelo antigênico - D'ippolito, João álvaro Costa (2009)
Neurocysticercosis is an important parasitic infection caused by the larvae form of the Taenia solium and it is a serious Public Health problem in Brazil. Because of its pleomorfic aspects the diagnosis of neurocysticercosis is difficult to confirm and its depends on the combination of information obtained from clinical examination, neuroimaging studies, epidemiological data and immunological tests. Computer tomography and magnetic resonance imaging techniques are considered golden standards for the diagnoses of neurocysticercosis, but those are inaccessible to the great majority of the population where neurocysticercosis is endemic. Immunodiagnostic techniques could help and complement the information obtained with computer tomography and magnetic resonance imaging exams for a definitive diagnosis of neurocysticercosis. So, the objective of this study was to standardize and evaluate an ELISA method using synthetic peptides obtained from the GP14 glycoprotein of Taenia crassiceps cysticerci for antibody detection in serum samples from patients suspected of having neurocysticercosis. Two biotinylated peptides were prepared and they were used as antigens in the ELISA test (ELISA-Pepbiot). In the evaluation, the ELISA-Pepbiot was compared to other methods already standardized: EITB using antigens derived from Taenia solium and T. crassiceps and ELISA employing Taenia crassiceps cysticercus glycoprotein antigen. Two distinct groups of patients suspect of having neurocysticercosis was evaluated in this study. The first (NCA group), it was composed of 24 patients who were submitted to computer tomography and magnetic resonance imaging exams. The second (NCB group), it was composed of 16 patients without imaging exams. Using the EITB-Tso results as gold standard, six out of the 24 serum samples from group NCA were positive. In the same group of patients, EITB-Tcra reacted with five sera, the ELISA-ConATcra with ten and the ELISA-Pepbiot reacted with seven. Taking in account only the results from patients with active neurocysticercosis or with type I and type II classification, ELISA-Pepbiot detected four serum samples out of nine, while all other tests reacted only with three serum samples. All serum samples from healthy individuals or patients with other parasitic infections were not reactive in the ELISA-Pepbiot. The use of synthetic peptides derived from Taenia crassiceps peptides could be an important alternative source of antigens to be used in immunological tests. The combination of both ELISA and EITB techniques can help to the neurocysticercosis diagnoses. Key words: ELISA. Immunodiagnostic. Neurocysticercosis. Taenia crassiceps.